Rahn Based on Tawarruq Model: Evidence from Malaysia - Md Nor, Mohd Zakhiri; Mohamad, Ani Munirah; Md Isa@ Yusuff, Yusramizza; Md Isa, Mohamad Yazid (2022)
Rahn is a supporting contract and has become a tool for the public to get easy micro-financial assistance. However, the conventional and rahn are under different regulators. Recently, the rahn industry in Malaysia needs to migrate from qard to the tawarruq concept. This paper begins with the background of the rahn industry in Malaysia. This paper examines the concept of the based tawarruq model. This paper also analyses the modus operandi of rahn under the qard and tawarruq model and YaPEIM as a case study. This paper is qualitative. The data is analysed by using content and comparative analysis. This paper found that the practice varies through the practice of rahn based on tawarruq in terms of profit rate. The operator still charges profit based on the amount of marhun as the practice during rahn based on qard. However, the operator now charges the profit based on the amount of tawarruq disbursed to the customer.